Hygiene and labour protection of medical staff under conditions of the pandemic COVID-19 overcoming (first message) - Yavorovskyi, O.P.; Shkurba, A.V.; Skaletskyi, Yu.M.; Brukhno, R.P.; Kharchuk, L.V.; Bugro, V.I.; Rygan М.М. (Environment & Health, 2020)
Objective: We assessed the conditions of the work of medical personnel under conditions of the coronavirus COVID-19 pandemic and determined the risks associated with them. Materials and methods: We used bibliographic, hygienic, questionnaire and mathematical methods in the study. The results of our own observations, questionnaires for a survey of medical workers, data of the WHO, Ministry of Health of Ukraine, Center for Public Health of the Ministry of Health of Ukraine, the State Labour Service of Ukraine, data of the State Statistics Service of Ukraine and thematic scientific sources of information were used as a material for the study. Results: The work of medical workers, involved inthe COVID-19 pandemic overcoming, is classified as dangerous (extremal). The risk of infection of medical personnel with the SARS-CoV-2 virus is increased with a deficiency of personal protective equipment for medical workers and its wrong application. The work under dangerous conditions of work at the healthcare institutions leads to a high incidence of COVID-19 in medical workers. Nursing personnel (38.43%), junior nursing staff (22.69%), anaesthetists (5.87%) predominate among medical workers with acute occupational disease COVID-19. Conclusions: The analysis of the results of performed studies allowed to make a conclusion that measures for the prevention of the incidence of COVID-19 in medical workers and measures for the improvement of the safety of the hospital environment should be aimed at more stringent compliance with national legislation and regulatory-and-methodological requirements for the protection of the conditions of workin medical personnel and infection control at the healthcare institutions